2023
DOI: 10.1101/2023.03.07.531563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

β-carotene accelerates the resolution of atherosclerosis in mice

Abstract: β-carotene oxygenase 1 (BCO1) catalyzes the cleavage of β-carotene to form vitamin A. Besides its role in vision, vitamin A regulates the expression of genes involved in lipid metabolism and immune cell differentiation. BCO1 activity is associated with the reduction of plasma cholesterol in humans and mice, while dietary β-carotene reduces hepatic lipid secretion and delays atherosclerosis progression in various experimental models. Here we show that β-carotene also accelerates atherosclerosis resolution in tw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…The studies have shown that β-carotene can even help alleviate atherosclerosis in mice. 45 Initially absent in Y. lipolytica, researchers successfully introduced key genes involved in the β-carotene synthesis pathway, including multiple copies of CARRP and CARB, as well as essential genes such as GGS1, HMGR, and ERG13 from the MVA pathway. This led to the production of 408 mg/L of β-carotene in shake flasks and a remarkable 4.5 g/L in a 5 L bioreactor.…”
Section: ■ Synthesis Of Terpenoidsmentioning
confidence: 99%
“…The studies have shown that β-carotene can even help alleviate atherosclerosis in mice. 45 Initially absent in Y. lipolytica, researchers successfully introduced key genes involved in the β-carotene synthesis pathway, including multiple copies of CARRP and CARB, as well as essential genes such as GGS1, HMGR, and ERG13 from the MVA pathway. This led to the production of 408 mg/L of β-carotene in shake flasks and a remarkable 4.5 g/L in a 5 L bioreactor.…”
Section: ■ Synthesis Of Terpenoidsmentioning
confidence: 99%